2020
DOI: 10.1108/jpbm-08-2019-2544
|View full text |Cite
|
Sign up to set email alerts
|

Co-creating consistent brand identity with employees in the hotel industry

Abstract: Purpose This paper aims to investigate how brand identity is co-created, with a specific focus on how employees contributed to the process in a five-star hotel setting. The focus of this study is on understanding how two hotels planned and executed their brand identity strategy simultaneously, differentiating one from the other and how employees actively participated in this process. Design/methodology/approach A longitudinal case study approach was adopted, centred on building the identity of two luxury hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…Therefore, well-established and reported link between CSR and total quality management from hotel industry in other jurisdictions (Jalilvand et al , 2018) is not confirmed by this Czech case study. Further, this study indicates that the potential of sustainable brand co-creation is much less developed in Czech hotel industry than in other jurisdictions, see highly developed and digitalized Asian countries (Chung and Byrom, 2020). Finally, these consequences are rather determined by the situation caused by the COVID-19, i.e.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, well-established and reported link between CSR and total quality management from hotel industry in other jurisdictions (Jalilvand et al , 2018) is not confirmed by this Czech case study. Further, this study indicates that the potential of sustainable brand co-creation is much less developed in Czech hotel industry than in other jurisdictions, see highly developed and digitalized Asian countries (Chung and Byrom, 2020). Finally, these consequences are rather determined by the situation caused by the COVID-19, i.e.…”
Section: Resultsmentioning
confidence: 81%
“…These challenges and their addressing involve basically each and every internal stakeholder. Especially the role of employees and their (un)readiness to reconcile the brand co-creation with these challenges (Chung and Byrom, 2020) and to go even more vigorously for mutually supported CSR and total quality management in the hotel industry is pivotal (Jalilvand et al , 2018). As well the growing role of the impact of social enterprises, including those from the hotel industry, on the economy in the Czech Republic needs to be appreciated (Tausl Prochazkova and Noskova, 2020).…”
Section: Overview Of the Literature Legislative And Analytical Frameworkmentioning
confidence: 99%
“…The brand meaning building process involves the identification of the components of the brand identity and the signalling to external audiences to create images (Veloutsou and Delgado-Ballester, 2018). The brand support team uses this internally shared set of symbols and associations (brand identity) as a basis of all decisions about the brand, using primarily marketing tactics, signalling to the market what the brand ideally means to its producer (Chung and Byrom, 2021). Signals originating not only from the brand team but also from other uncontrolled sources that refer to or are associated with the brand are received and processed by consumers who form specific views about the brand (brand image) related with a particular encounter or mention of the brand.…”
Section: Brand Relationships and The Consumer Mindsetmentioning
confidence: 99%
“…The involvement of local communities (Daldanise, 2020), particularly local residents (Braun et al, 2013;Casais and Monteiro, 2019;Rebelo et al, 2020) or employees from the local hospitality industry (Chung and Byrom, 2021) engaged in transferring their collective experiences, feelings and aspirations to the place brand (Ind et al, 2020), activates these stakeholders as ambassadors of the place marketing process (Golestaneh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This applies equally to tourism destination and place branding (Giannopoulos et al , 2021; Jain et al , 2021), considering the relevant outcome in brand equity (Buhalis and Park, 2021; Mohammadi et al , 2021). The involvement of local communities (Daldanise, 2020), particularly local residents (Braun et al , 2013; Casais and Monteiro, 2019; Rebelo et al , 2020) or employees from the local hospitality industry (Chung and Byrom, 2021) engaged in transferring their collective experiences, feelings and aspirations to the place brand (Ind et al , 2020), activates these stakeholders as ambassadors of the place marketing process (Golestaneh et al , 2021). There are examples of co-creation practices that have been able to effectively integrate key stakeholders through bottom-up approaches in place branding (Pryor and Grossbart, 2007; Hudson et al , 2017), allowing public participation in the process of identifying place identity and brand design (Kavaratzis and Hatch, 2013).…”
Section: Introductionmentioning
confidence: 99%